The effects of COVID-19 on perioperative morbidity and mortality in patients with hip fractures: a multicentre cohort study. (September 2020) - Kayani, Babar; Onochie, Elliot; Patil, Vijay; Begum, Fahima; Cuthbert, Rory; Ferguson, David; Bhamra, Jagmeet S.; Sharma, Aadhar; Bates, Peter; Haddad, Fares S.
Abstract : Aims: During the COVID-19 pandemic, many patients continue to require urgent surgery for hip fractures. However, the impact of COVID-19 on perioperative outcomes in these high-risk patients remains unknown. The objectives of this study were to establish the effects of COVID-19 on perioperative morbidity and mortality, and determine any risk factors for increased mortality in patients with COVID-19 undergoing hip fracture surgery. Methods: This multicentre cohort study included 340 COVID-19-negative patients versus 82 COVID-19-positive patients undergoing surgical treatment for hip fractures across nine NHS hospitals in Greater London, UK. Patients in both treatment groups were comparable for age, sex, body mass index, fracture configuration, and type of surgery performed. Predefined perioperative outcomes were recorded within a 30-day postoperative period. Univariate and multivariate analysis were used to identify risk factors associated with increased risk of mortality. Results: COVID-19-positive patients had increased postoperative mortality rates (30.5% (25/82) vs 10.3% (35/340) respectively, p < 0.001) compared to COVID-19-negative patients. Risk factors for increased mortality in patients with COVID-19 undergoing surgery included positive smoking status (hazard ratio (HR) 15.4 (95% confidence interval (CI) 4.55 to 52.2; p < 0.001) and greater than three comorbidities (HR 13.5 (95% CI 2.82 to 66.0, p < 0.001). COVID-19-positive patients had increased risk of postoperative complications (89.0% (73/82) vs 35.0% (119/340) respectively; p < 0.001), more critical care unit admissions (61.0% (50/82) vs 18.2% (62/340) respectively; p < 0.001), and increased length of hospital stay (mean 13.8 days (SD 4.6) vs 6.7 days (SD 2.5) respectively; p < 0.001), compared to COVID-19-negative patients. Conclusion: Hip fracture surgery in COVID-19-positive patients was associated with increased length of hospital stay, more admissions to the critical care unit, higher risk of perioperative complications, and increased mortality rates compared to COVID-19-negative patients. Risk factors for increased mortality in patients with COVID-19 undergoing surgery included positive smoking status and multiple (greater than three) comorbidities.